2017
DOI: 10.9734/arrb/2017/33162
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Auxins on Rooting of Rosemary, Sage and Elderberry

Abstract: Aims: The aim of research is to examine the influence of auxins IAA, IBA, NAA and commercial rooting product on rooting of cuttings from rosemary (Rosmarinus officinialis L.), sage (Salvia officinialis L.) and elderberry (Sambucus nigra L). Study Design: Completely randomized design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 18 publications
(15 reference statements)
0
2
1
5
Order By: Relevance
“…Auksin diproduksi tanaman pada jaringan meristem, dimana auksin mampu meningkatkan persentase pembentukan akar, mempercepat inisiasi akar, meningkatkan jumlah dan kualitas akar dan mempromosikan pengembangan akar yang seragam (Blythe et al, 2007;Khasin et al, 2018;Gudeva et al, 2017 (Pacurar et al, 2014).…”
Section: Pendahuluanunclassified
“…Auksin diproduksi tanaman pada jaringan meristem, dimana auksin mampu meningkatkan persentase pembentukan akar, mempercepat inisiasi akar, meningkatkan jumlah dan kualitas akar dan mempromosikan pengembangan akar yang seragam (Blythe et al, 2007;Khasin et al, 2018;Gudeva et al, 2017 (Pacurar et al, 2014).…”
Section: Pendahuluanunclassified
“…Gudeva ve ark. [17], IAA, IBA, NAA ve ticari köklendirme ürünleri ile yapılan bir çalışmada en iyi köklenme etkisinin, IBA (% 54) ve NAA (% 50) uygulamalarıyla elde edildiğini, bununla birlikte en fazla kök uzunluğunun ticari köklendirme ürününden (5.60 cm) ve kontrol grubu çeliklerinden (5.25 cm) işlem gördüğü belirtmişlerdir.…”
Section: Lavanta (Lavandula Angustifolia)unclassified
“…Gudeva ve ark. [17], IAA, IBA, NAA ve ticari köklendirme ürünleri ile yaptıkları çalışmada biberiye çeliklerinde en iyi simülatif etkiyi IBA'nın gösterdiğini, çelik uzunluğunun 25.17 cm, köklenmiş çelik sayısının 46 adet, köklenme oranının %92 olduğu bu uygulama, kontrol grubu dâhil diğer uygulamalara oranla bir hayli yüksek olduğunu bildirmişlerdir.…”
Section: Biberiye (Rosmarinus Officinalis)unclassified
See 1 more Smart Citation
“…Massoud et al (2017) concluded that using of natural products (minerals and amino acid compound) was better than IBA rooting auxin and resulted in enhancing rooting, vegetative growth and chemical constituents of rosemary cuttings. The application of auxin at 5 ppm IBA positively affected rosemary rooting of cuttings by 92% (Gudeva et al, 2017). Vasca-Zamfir et al (2018) evaluate the impact of rhizogenic biostimulator Clonex gel treatments on rooting of rosemary cuttings and found that, the biostimulator increased rooting percentage of cuttings and increasing of total chlorophyll and in the leaves.…”
Section: Introductionmentioning
confidence: 99%